Pencegahan Anemia dengan Pemberian Zat Besi (Fe) pada Ibu Hamil - Amelia Erawaty Siregar; Sri Rezeki; Erin Padilla Siregar (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Anemia is a widespread public health problem associated with increased mortality and morbidity, especially in pregnant women. In both developed and developing countries, some women experience anemia during pregnancy. Usually non-pregnant women have normal hemoglobin of 12-15%. According to WHO, the incidence of anemia in pregnancy ranges from 20% to 89% by setting HB <11 gr% (h/dl). The rate of anemia in pregnancy occurs 3.8% in the first trimester, 13.6% in the second trimester and 24.8% in the third trimester (Manuaba, 2012). The counseling method on preventing anemia by providing iron (Fe) to pregnant women is used in the community service program. The community service event was presented by twenty pregnant women from Bangun Rejo Village aged 20 to 35 years. After the counseling activity, pregnant women from Bangun Rejo Village understood more about anemia in pregnant women. This can be seen from the increase in their post-test scores compared to their pre-test. The pre-test results showed that most participants answered incorrectly, with an average score of 35; the post-test results showed an increase in knowledge, with an average score of 80. After attending the counseling and completing the post-test, the last participants underwent an Hb examination, which was guided by a gymnastics instructor and documented via video.